1996
DOI: 10.1117/12.227699
|View full text |Cite
|
Sign up to set email alerts
|

Group refractive index measurement of dry and hydrated type I collagen films using optical low-coherence reflectometry

Abstract: The group refractive index and physical thickness of dry and hydrated type I collagen films are measured using optical low-coherence reflectometry. The average value for the group refractive index of dry and fully hydrated collagen films at o = 850 nm is, respectively, 1.53 Ϯ 0.02, and 1.43 Ϯ 0.02. The physical thickness of type I collagen films nearly doubles when going from the dry (56 m) to hydrated (118 m) state. Keywords reflectometry; hydrated type I collagen films; group refractive index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 25 publications
2
46
1
Order By: Relevance
“…It has been reported that the group refractive index of the dry collagen is about 1.53 at 850 nm. 19 Our fitted refractive index of the main substrate matches well to this value and is consistent with the fact that collagen fibers are the major components in cornea. Overall, the corneal thickness, hydration, and refractive index changes during the storage were accurately monitored by OCT images with those changes strongly reflecting the effect of the storage media on the cornea structures as well as functions.…”
Section: Journal Of Biomedical Opticssupporting
confidence: 71%
“…It has been reported that the group refractive index of the dry collagen is about 1.53 at 850 nm. 19 Our fitted refractive index of the main substrate matches well to this value and is consistent with the fact that collagen fibers are the major components in cornea. Overall, the corneal thickness, hydration, and refractive index changes during the storage were accurately monitored by OCT images with those changes strongly reflecting the effect of the storage media on the cornea structures as well as functions.…”
Section: Journal Of Biomedical Opticssupporting
confidence: 71%
“…36 The RI of water content is close to 1.33, whereas the dry collagen fibrils have a higher RI of 1.53. 37 This special biochemical constitution of normal AC enables the increasing trend of RI along depth direction. The orientation of collagen contents has strong influence to the light propagation.…”
Section: Ri Distribution With Depthmentioning
confidence: 99%
“…Anhydrous glycerol, such as was used in these studies, has a refractive index of 1.47 [21]. Collagen has a refractive index of 1.43 in the hydrated state and 1.53 in the dry state [22]. In the native state the extracellular¯uid has a refractive index of 1.35 [23]; however, the presence of glycerol or the loss of water due to glycerol will cause the extracellular¯uid refractive index to become larger, better index matching collagen and other tissue constituents.…”
Section: Microscopic Observationmentioning
confidence: 99%